Virtual reality utilization for left atrial appendage occluder device size prediction. Issue 4 (April 2023) - Tejman-Yarden, Shai; Freidin, Dor; Nagar, Netanel; Parmet, Yisrael; Abed, Muhamed; Vazhgovsky, Oliana; Yogev, David; Ganchrow, Dov; Mazor-Drey, Efrat; Chatterji, Sumit; Beinart, Roy; Barbash, Israel; et al.
Abstract: Aim: To explore the feasibility and accuracy of virtual reality (VR) derived from cardiac computed angiography (CCTA) data to predict left atrial appendage occlusion (LAAO) device size. Method: Retrospective data of patients who underwent LAAO according to clinical indication were reviewed; all patients underwent a pre-procedural CCTA. Measurements of the left atrial appendage (LAA) orifice diameters by CCTA, VR, and transesophageal echocardiography (TEE) (acquired during the procedure) were compared to the implanted device size. The LAA perimeter was calculated using the Ramanujan approximation. Statistical analyses included Lin's Concordance Correlation Coefficient ( ρ c ), the mean difference, and the mean square error (MSE). Results: The sample was composed of 20 patients (mean age 75.7 ± 7.5 years, 60% males) who underwent successful LAAO insertion (ACP™ N = 8, Watchman™ N = 12). The CCTA, VR, and TEE maximal diameter ρ c was 0.52, 0.78 and 0.60, respectively with mean differences of +0.92 ± 4.0 mm, −1.12 ± 2.3 mm, and −3.45 ± 2.69 mm, respectively. The CCTA, VR, and TEE perimeter calculations ρ c were 0.49, 0.54, and 0.39 respectively with mean differences of +4.69 ± 11.5 mm, −9.88 ± 8.0 mm, and −16.79 ± 7.8 respectively. Discussion: A VR visualization of the LAA ostium in different perspectives allows for a better understanding of its funnel-shaped structure. VR measurement of the maximal ostium diameter had the strongest correlation with the diameter of the inserted device. VR may thus provide new imaging possibilities for the evaluation of complex pre-procedural structures such as the LAA.